Human Population Growth and Its Effect on the Forest Ecosystem - Gupta, Ashwani Kumar (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Population growth is the increasing, in the number of people in a population dispersed group. Population growth alongside increased consumption is a driver of environmental concerns, such as biodiversity loss and climate change, due to resources utilized in human development. Natural woodland area making it a suitable place for a survival of biotic and abiotic components is usually termed a forest ecosystem. A forest ecosystem consists of various plants, animals, and other microorganisms, making it a natural habitat for them. Humans are Converting forest to agricultural and urban areas, exploiting species, and fragmenting wild lands, changed the demographic structure of forests, altered habitat, degraded the environment with atmospheric and soil pollutants, introduced exotic pests and competitors, and domestic favored species. Due to increasing human population on planet, the human habituated areas are increased and forest areas are decreased, This behavior causes deforestation. The deforestation affects on the forest animals ecosystem. The domestic animals like dogs. And cats can attack on the forest animals for their feeding and the forest Carnivores can attack on the domestic animals, cattle etc. as well as also on the human beings. Changing human behavior against forest animals, the hunting behavior against forest animals is also developed.